Management of Government Owned Bus Companies Services in Ghana: Application of Scientific Methods Analysis in Perspective (Journal of Management & Business, 2024)
Government owned transport companies in Ghana ought to up their management decisions on the factors surrounding the Supportive Work Culture of their staffs especially, the drivers. Without drivers there will be no movement of buses to various destinations. Besides, it is the drivers that come into contact with customers or passengers every day and faces a lot of safety issues and other road challenges such as traffic and bad roads and bad road networks. Hence, since drivers have been agitating and demonstrating for better conditions of service, calls for further investigation into the sector, it means job satisfaction has been a problem for them. Since the outer loadings and outer weights affects many of the constructs. This research model tested showed that employees work behaviour and commitment have influence on their Job Satisfaction at work. This also reveals that the Good Governance aspect needs much improvement to reflect the desire of the drivers in order to achieve the company objectives. The Outer loadings of the constructs for the various variables showed both weak and higher Outer Loadings but a combination of all these was significant in almost all the measurements results.
Keywords: Government Buses; Public Transportation; Private Bus; Path Coefficients; Indirect Effects; Total Effects; Reverse Scores